PENEGAKAN HUKUM ILLEGAL FISHING - Harliza, Elvinda Rima; Michael, Tomy (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Indonesia is a country that has a large area in the waters, so that foreign fishermen always escape illegal fishing activities. This theft occurred because of the lack of attention from the water inspectors. Until now, fish theft is still common. Because of this, Indonesia must suffer a huge loss of up to Rp 30 trillion each year. When viewed with a percentage reaching 25% with the amount of 1.6 million tons annually. These problems have resulted in many parties being harmed because of illegal fishing, so law enforcement is needed to regulate these actions. This is the reason the author writes a journal with the title Illegal Fish Enforcement. With the formulation of the problem as follows: